2022
DOI: 10.1093/brain/awac009
|View full text |Cite
|
Sign up to set email alerts
|

A neural network for tics: insights from causal brain lesions and deep brain stimulation

Abstract: Brain lesions are a rare cause of tic disorders. However, they can provide unique insights into tic pathophysiology and can also inform on possible neuromodulatory therapeutic targets. Based on a systematic literature review, we identified 22 cases of tics causally attributed to brain lesions and employed ‘lesion network mapping’ to interrogate whether tic-inducing lesions would be associated with a common network in the average human brain. We probed this using a normative functional connectome acquired in 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 79 publications
2
33
0
Order By: Relevance
“…Lesions causing cervical dystonia are connected to the cerebellum and sensory cortex, converging with connectivity with the optimal globus pallidus DBS electrode location connectivity in patients with idiopathic generalized or cervical dystonia [23]. Similarly, Ganos, Al-Fatly et al [5 ▪ ] recently showed that connectivity between DBS sites and a network connected to lesions causing tics significantly predicted clinical improvement in patients. In depression, therapeutic brain stimulation (both invasive and noninvasive) and brain lesions converged on common circuits [28 ▪ ].…”
Section: Linking Lesion Network Mapping Findings To Treatment Targetsmentioning
confidence: 89%
See 4 more Smart Citations
“…Lesions causing cervical dystonia are connected to the cerebellum and sensory cortex, converging with connectivity with the optimal globus pallidus DBS electrode location connectivity in patients with idiopathic generalized or cervical dystonia [23]. Similarly, Ganos, Al-Fatly et al [5 ▪ ] recently showed that connectivity between DBS sites and a network connected to lesions causing tics significantly predicted clinical improvement in patients. In depression, therapeutic brain stimulation (both invasive and noninvasive) and brain lesions converged on common circuits [28 ▪ ].…”
Section: Linking Lesion Network Mapping Findings To Treatment Targetsmentioning
confidence: 89%
“…Similarly, LNM has recently been applied to other long-standing neurological mysteries, including motor/vocal tics, blindsight, and pathological laughter and crying, characterized by inappropriate outbursts of laughter and/or weeping [5 ▪ ,13,22 ▪ ]. In each of these conditions, prior neuroimaging studies have provided heterogeneous results and causal lesions are scattered throughout many different regions in the brain, leaving the neural substrate unknown.…”
Section: Unravelling Clinical Entitiesmentioning
confidence: 99%
See 3 more Smart Citations